Whethering Station: Thin surface, thick surface - de Manincor, John (Interstices: Journal of Architecture and Related Arts, 2017)
The Whethering Station project forms part of the PhD by Practice at RMIT University. Titled Surface and the spaces between, the thesis explores the idea of “surface and space as reciprocal and correspondent entities”, a proposition by Nader Tehrani and Monica Ponce de Leon in their seminal essay Versioning: Connubial Reciprocities of Surface and Space (Tehrani/Ponce de Leon, 2002: 18-28). The project continues a “contest” between structure and skin (Leatherbarrow/Mostafavi 2002: 7) through the creation of a modest pavilion using novel fabrication processes for thin, double-curved composite materials. This thin surface blurs the distinction between cladding and lining, obliterating the “mute workings of the section” (Blais, 1996). The work explores the possibility of occupying a surface implied by a six millimeter “thin” line.